2010
DOI: 10.1177/11207000100200s707
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results after anterior mini-open approach for femoroacetabular impingement in early degenerative stage

Abstract: We describe our modified anterior mini-invasive technique and results obtained in our first consecutive 117 cases in 105 patients. To assess the influence of preoperative Tönnis degenerative stage, cases were divided into group A (Tönnis 0, 32 hips), B (Tönnis 1, 61 hips), and C (Tönnis 2, 24 hips). The clinical score Dexeus combined score (DCS) was used preoperatively, 3 months, 6 months, and every year after operation. At 3-month follow-up, impingement test results improved significantly in 30 hips of group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 40 publications
1
24
0
6
Order By: Relevance
“…18 Surgery has been shown to improve pain and function scores in 65%-96% of patients at short-term follow up. 19,20 Risk factors for poor outcome have been found to include patients with advanced arthrosis (Tonnis grade 2 or 3) on preoperative imaging 21,22 and either chondral or labral disease identified intraoperatively. 23 Cam-type impingement is associated with cartilage delamination.…”
Section: Discussionmentioning
confidence: 99%
“…18 Surgery has been shown to improve pain and function scores in 65%-96% of patients at short-term follow up. 19,20 Risk factors for poor outcome have been found to include patients with advanced arthrosis (Tonnis grade 2 or 3) on preoperative imaging 21,22 and either chondral or labral disease identified intraoperatively. 23 Cam-type impingement is associated with cartilage delamination.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the results of using mini-open technique in the treatment of FAI [8, 9, 19]. Most of the authors used anterior Hueter approach on an extension table or fracture table, taking the advantage of intermuscular and internervous dissection [18].…”
Section: Discussionmentioning
confidence: 99%
“…The use of mini-open technique with arthroscopic assistance is less often reported in the literature [18]. The advantages of this approach include both minimal soft tissue invasion and improved quality of the osteochondroplasty by direct visualization on femoral head and neck that would otherwise only be obtained with surgical dislocation [19]. The assistance of arthroscopy provided detailed visualization and management of chondral and labral injuries in a small wound [20].…”
Section: Introductionmentioning
confidence: 99%
“…A recent case series demonstrated that patients with Tönnis 2 arthritis had significantly less chance of improvement (58%) than patients with Tönnis 0 or 1 arthritis (94% and 95%, respectively). 8 Even slight joint space narrowing, however, may indicate severe cartilage damage, which will affect axial loading and limit the possibility of improvement. 9 Therefore, patients with FAI and significant degenerative joint disease should be treated nonoperatively until they are ready for a total hip replacement.…”
Section: Surgical Candidate Selectionmentioning
confidence: 99%
“…Postoperatively, patients are able to quickly return to full weight bearing activity at 6 weeks. Ribas et al 8 published a series of 117 hips that underwent mini-open FAO that shows significant clinical and functional improvement, especially those with Tönnis 1 and Tönnis 2 arthritis. From our institutional experience, of 82 patients that underwent mini-open direct anterior FAO by the senior author (J.P.) that have reached at least 1 year of follow-up, 78 experienced significant improvements in their function, measured by modified Harris hip score, SUSHI (ie, SUper Simple HIp) score, and UCLA score.…”
Section: Outcomes Of Surgerymentioning
confidence: 99%